Analisis Kesalahan Siswa Berdasarkan Teori Newman dalam Menyelesaikan Soal Cerita Matematika Sekolah Dasar - Hamdana Hadaming; Andi Ardhila Wahyudi (Jurnal Ilmu Pendidikan Dasar Indonesia, 2022)
This research is motivated by the low learning outcomes of second grade students of SD Bawakaraeng in mathematics subjects, one of which is in learning math story problems. The problem that arises is what are the mistakes and causes of student errors in solving math story problems based on Newman's procedure at SD Bawakaraeng. The purpose of this study was to describe students' mistakes in solving math story problems and describe the causes of students' errors in solving math story problems based on Newman's procedure at SD Bawakaraeng. The student error analysis procedure used is the Newman procedure. This type of research is qualitative research. Data was collected by using test and interview techniques with 5 students as research subjects. The data analysis technique used Milles and Huberman model analysis. Test the validity of the data is done by triangulation technique. The results showed that the data were analyzed using descriptive analysis, correlation analysis The conclusion was obtained, students tried to implement the Newman procedure when working on math problems. However, due to lack of familiarity, there are often steps that are not taken, namely at the step of understanding the problem, transformation and process skills. As for the 5 steps of the Newman procedure, the results obtained are step 1) reading errors, none of the students made any type of reading errors; step 2) misunderstanding, new mistakes made by students when understanding the problem as many as 4 students; step 3) transformation, on the transformation error of students who make mistakes as much as 1 student; Step 4) process skills, all students make mistakes; and step 5) writing answers, as many as 4 students who made mistakes. There are 3 factors that cause students to make mistakes, namely: 1) difficulty understanding the problem; 2) do not understand the concept and operation of division; 3) and for forgetting and not being careful. The solution offered to minimize student errors in solving story problems is to increase the practice of working on story questions and make story questions in a more communicative language.